The Influence of Physical Training on Breast Cancer: The Role of Exercise-Induced Myokines in Regulating Breast Cancer Cell Growth and Survival - Natarajan, Anirudh; Pradhan, Rashmita; Dieterich, Walburga; Schwappacher, Raphaela; Reljic, Dejan; Herrmann, Hans Joachim; Neurath, Markus; Hack, Carolin; Beckmann, Matthias; Zopf, Yurdagül (International Journal of Molecular Sciences, 2024)
The beneficial impact of physical training in lowering cancer risk is well known. However, the precise mechanisms linking physical training and cancer are not fully understood. Skeletal muscle releases various myokines that seem to possess a direct anti-tumor effect. Although breast cancer (BC) is the prevalent form of cancer among women on a global scale, only limited data are available about the secretion of myokines following exercise in patients with BC. To study the effects of exercise on BC, the blood samples of patients with varied stages of BC were analyzed after 12 weeks of resistance training with whole-body electromyostimulation (WB-EMS). Following the training period, we observed that resistance training helps these patients to improve their physical characteristics and performance function by increasing skeletal muscle mass and strengthening their hand grip. Notably, the patient’s serum was found to inhibit the growth and promote the apoptosis of BC cells in vitro. Moreover, the conditioned medium collected from in vitro stimulated human myotubes using electric pulse stimulation (EPS), an in vitro simulation of WB-EMS training, induced the cell death of BC cells. These results highlighted the direct cancer-protective effects of activated skeletal muscle. In line with our observed effects of serum from exercise-trained pancreatic and prostate cancer patients, the growth of BC cells was notably inhibited when supplemented directly with recombinant myokines C-X-C motif ligand 1 (CXCL1), Interleukin 10 (IL10), and C-C motif chemokine ligand 4 (CCL4). Notably, treatment with these myokines also increased the expression of caspase 3/7 (Casp3/7), resulting in enhanced BC cell death. Our data strongly suggest that physical exercise has a positive impact on skeletal muscle mass and hand grip strength in BC patients, along with a significant anti-tumor effect in BC cells. This shows promising potential for considering sports and physical training as supportive therapies for achieving more impactful cancer treatment.
CRIS-Team Scopus Importer:2024-11-22
Keywords: apoptosis; breast cancer; electric pulse stimulation; myokines; proliferation; resistance training; whole-body electromyostimulation